CIVIL - MILITARY COOPERATION - TOOL ENHANCING THE SURGICAL TEAMS' CAPABILITIES IN DISASTER MEDICAL SUPPORT - Rostislav Kostadinov (Peytchinski Publishing, 2017)
In light of recent world disastrous events, it is increasingly clear that all health professionals need to become more proficient in the recognition, diagnosis, and treatment of mass casualties under an all-hazards approach to disaster management and response From the author's experience, the cooperation between civil and military medical surgical teams could benefit their educational and training processes. The aim of this article is to present the areas where the military medical teams training and capacities could enhance the civilian surgical teams' preparedness and effectiveness during disaster relief operations. Descriptive and comparative methods were applied in order to determine the disasters' features with impact on medical support and related to them specific disaster medicine requirements towards medical teams. By cluster analysis, the capabilities of the military medical teams and civilian surgical teams to respond to these requirements are discussed in order to describe the areas for military-civil cooperation that could enhance the medical support efficacy. The possible areas, where the civil-military cooperation could enhance the surgical teams' capabilities for disaster medical assistance provision are described.